Gradual Colonic Impaction of a Chicken Bone Associated with Inflammatory Pseudotumor Formation and Nonocclusive Colon Ischemia. (27th January 2014) - Fosi, Stefania; Altobelli, Simone; Bindi, Alessio; Villa, Massimo; De Sanctis, Flavio; Montuori, Mauro; Ricciardi, Edoardo; Rossi, Piero; Petrella, Giuseppe; Simonetti, Giovanni
Abstract : Foreign body (FB) ingestion is a common clinical problem and most FBs pass through the gastrointestinal tract without the need for intervention. A wide spectrum of clinical presentations may be possible and these can be either acute or chronic. We present a case of an 83-year-old woman featuring insidious abdominal discomfort who was hospitalized in our institution due to worsening symptoms. She underwent contrast-enhanced computed tomography (CT) evaluation which showed the presence of a significant parietal thickening of the transverse and descending colon, a mesenteric loose tissue imbibition, venous engorgement, and no filling defect of visceral arteries, suggesting a condition of nonocclusive colon ischemia. A hyperdense FB was identified in the sigma and was associated with a small pseudotumoral mass. The patient underwent surgical exploration which confirmed the hypoperfusional state of the colon, showing the presence of a chicken bone perforating the sigma and lying in the context of a pseudotumoral mass. Our experience shows how contrast-enhanced CT is feasible and can be strongly recommended as a first-line imaging tool on suspicion of colon ischemia and also how it can easily identify the underlying cause, in our case a FB sealed perforation of the sigma with pseudotumoral mass formation.